Evaluating the Net Benefits of Macroprudential Policy : A Cookbook - Arregui, Nicolas (IMF Working Papers; Working Paper ;, 2013)
The paper proposes a simple, new, analytical framework for assessing the cost and benefits of macroprudential policies. It proposes a measure of net benefits in terms of parameters that can be estimated: the probability of crisis, the loss in output given crisis, policy effectiveness in bringing down both the probability and damage during crisis, and the output-cost of a policy decision. It discusses three types of policy leakages and identifies instruments that could best minimize the leakages. Some rules of thumb for policymakers are provided.